Chemical, Bioactive and antioxidant properties of Alhydwan (Boerhavia elegana Choisy) Seeds- A review - Albisher, Afnan Othman Mohammed; Mohammed, Asmahan Azhari Ali; Mohamed, Sahar Hasan Salah (Journal of agricultural, environmental and veterinary sciences, 2023)
In recent years, consumers have turned to natural foods, but this is not the case. Since synthetic preservatives are harmful to health, consumers demand partial or complete replacement of synthetic preservatives. Because of this, there is an increasing demand for the development of more natural alternatives to improve food shelf life and safety. Strategies for natural protection are gaining popularity in food mapping. New preservation methods focus on using environmentally friendly organic plants with antioxidant and antimicrobial properties to extend the safety and shelf-life of food. Since ancient times, medicinal plants have been used in almost all cultures to treat many ailments around the world. The genus Boerhavia is found around the world in tropical, subtropical in nature and temperate climates, including Mexico, as well as the United States, Africa, Asia, Indian Ocean islands, Pacific islands, and Australia.  Boerhavia plants are widely used by locals and physicians to treat hepatitis, urinary tract disorders, gastrointestinal disorders, inflammation, skin problems, infectious diseases and asthma. This review focuses on the bioactive compounds of Boerhavia elegana Choisy.
Keywords: Boerhavia elegana Choisy; chemical content; Antioxidant compounds